Control mechanisms and design for a 'coal-backfill-gangue' support system for coal mine gob-side entry retaining. (2018) - Ning, J.G.; Liu, X.S.; Tan, J.; Gu, Q.H.; Tan, Y.L.; Wang, J.
Gob-side entry retaining (GER) is an important technique for realising continuous development in coal mines in China. GER safety depends on the support of the coal wall, the gob-side backfill, the gangue in the goaf, and some auxiliary supports. However, field investigations have shown that the coal wall and gob-side supports fail easily during the second mining action, especially in the conditions of deep mining and hard main roof. To ensure the stability of a GER, this paper first establishes a deformation and control model for the 'coal-backfill-gangue' support system to determine the acceptable rotation angle of the lateral main roof. This model also determines the quantitative relationship between the roof pressure on the GER and the support forces provided by the support system. Then, based on the acceptable rotation angle of the lateral main roof, the quantitative design method for support system of the GER under different conditions is proposed. Finally, a field case study in the no. 16101 haulage roadway of the Binhu Coal Mine, China, is presented. After calculations, a 'flexible and rigid' composite material was used as the gob-side backfill and the specifications for the bolts in the coal wall were changed. Field observations showed that the improved supports can maintain stability of surrounding rocks of the haulage roadway. This research provides an effective design method for the 'coal-backfill-gangue' support system to be used in GER. [Received: May 20, 2017; Accepted: October 24, 2017]